Structure and Anti-HIV Activity of Betulinic Acid Analogues - Huang, Qiu-xia; Chen, Hong-fei; Luo, Xing-rui; Zhang, Yin-xiang; Yao, Xu; Zheng, Xing (Current medical science, 2018)
Summary Firstly discovered in 1980s, human immunodeficiency virus (HIV) continues to affect more and more people. However, there is no effective drug available for the therapy of HIV infection. Betulinic acid existing in various medicinal herbs and fruits exhibits multiple biological effects, especially its outstanding anti-HIV activity, which has drawn the attentions of many pharmacists. Among the derivatives of betulinic acid, some compounds exhibited inhibitory activities at the nanomolar concentration, and have entered phase II clinical trials. This paper summarizes the current investigations on the anti-HIV activity of betulinic acid analogues, and provides valuable data for subsequent researches.